Processing And Extracting Data From A Dataset For Artificial Intelligence IN Neural Radiance Fields.Traitement et extractiondes données d’un dataset via l’IA pour le Neural Radiance Fields - DEMANA FERIAL; GUESMIA ZINEB; BOUZIDI MOHAMMED REDHA (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE DEPARTEMENT : Département d’Electronique, 2024)
In this works the use of artificial intelligence techniques in image processing, with a focus on background removal in complex images such as trees. It analyzes the Roboflow platform as a powerful tool for data management and enhancement, demonstrating its use in transfer learning to improve model performance. Tools like Photoshop and deep learning techniques such as U-Net and GANs are also discussed, highlighting how Google Colab can be used effectively for prototyping models. The results show that AI significantly improves the accuracy and efficiency of background removal, reducing the manual effort required. The thesis works the continuous development of AI techniques to enhance image processing, paving the way for new and improved applications in the future.
Telecommunications and Networks